High temperature resistant thermal insulation fiber composite material and preparation method thereof

CN116675512BActive Publication Date: 2026-10-13JIANGSU LONGYE ENERGY SAVING TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310615900.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-29
Publication Date
2026-10-13
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

[0003]近年来已经出现了很多综合性能优异的隔热材料,但现有的隔热材料都很难同时兼具耐高温、高强度、低热导率等性能

Benefits of technology

[0030]本发明采用钛溶胶、硅溶胶以及高分子溶液的混合物静电纺丝成三维多孔状纳米纤维膜,然后煅烧将高分子材料去除留下残碳,仍能获得三维多孔状纳米纤维膜,煅烧对整体膜的形态无影响,能够得到柔性、三维多孔、耐高温的无机纳米纤维膜;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116675512B_ABST
    Figure CN116675512B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of heat-insulating fiber materials, and particularly relates to a high-temperature-resistant heat-insulating fiber composite material and a preparation method thereof, which has the structure of fiber sheet layers adhered to the two surfaces of a titanium / silicon / carbon inorganic composite nanofiber film layer; the preparation method comprises the following steps: (1) electrospinning and calcining to obtain the titanium / silicon / carbon inorganic composite nanofiber film layer; (2) preparing slurry and web-forming to obtain a wet sheet base; the slurry comprises aluminum silicate fibers, an infrared barrier agent, a binder and water; the infrared barrier agent is potassium hexatitanate whiskers and zirconium oxide; (3) sequentially stacking the wet sheet base, the titanium / silicon / carbon inorganic composite nanofiber film layer and the wet sheet base, and then pressing, dehydrating, drying and solidifying to obtain the high-temperature-resistant heat-insulating fiber composite material. The material has good tensile strength and can resist high temperature up to 1450 DEG C, and the thermal conductivity coefficient at room temperature is below 0.025 W / m*K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat-insulating fiber materials technology, specifically to high-temperature resistant heat-insulating fiber composite materials and their preparation methods. Background Technology

[0002] Kilns are used in the hot processing of industries such as metallurgy, building materials, ceramics, glass, chemicals, and electromechanical equipment. However, various kilns suffer from significant heat loss, and in most cases, their thermal efficiency is very low, with a heat energy utilization rate of less than 30%, indicating substantial potential for energy conservation. Using high-efficiency insulation materials can greatly reduce heat dissipation and heat storage losses, achieving energy-saving goals. Furthermore, the power industry urgently needs large quantities of insulation materials for pipeline insulation, building insulation, and energy conservation and consumption reduction in refrigeration facilities. In addition, in defense applications such as nuclear power and aerospace, materials are required not only to have good insulation properties but also high high-temperature resistance and a certain level of strength.

[0003] In recent years, many high-performance thermal insulation materials have emerged, but existing materials struggle to simultaneously possess properties such as high temperature resistance, high strength, and low thermal conductivity. For example, fiber-reinforced aerogel thermal insulation composites exhibit low thermal conductivity and excellent thermal insulation performance, but their strength and high-temperature resistance need improvement; fiber-reinforced porous ceramic thermal insulation materials offer good high-temperature resistance and a certain level of strength, but their thermal conductivity is relatively high; and fiber-reinforced oxide ceramic matrix composites possess high strength and good temperature resistance, but their thermal conductivity needs further reduction.

[0004] Therefore, how to coordinate the relationship between the strength, low thermal conductivity, and high temperature resistance of materials is the technical problem that this invention aims to solve. Summary of the Invention

[0005] To address the aforementioned technical problems, a high-temperature resistant heat-insulating fiber composite material and its preparation method are provided. The fiber composite material of this invention exhibits low thermal conductivity, good high-temperature resistance, and high strength.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0007] High-temperature resistant heat-insulating fiber composite material has the following structure:

[0008] The titanium / silicon / carbon inorganic composite nanofiber membrane has bonded fiber sheets on both surfaces;

[0009] The fiber sheet is made from the following raw materials: aluminum silicate fiber, infrared blocking agent, and binder; the infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide.

[0010] Furthermore, the preparation method of the titanium / silicon / carbon inorganic composite nanofiber membrane is as follows: the silicon source solution, the titanium source solution and the polymer solution are mixed evenly to form a spinning solution, which is then electrospun and calcined to obtain the membrane.

[0011] Furthermore, the electrospinning parameters are as follows: spinning voltage 15-20kV, spinning solution injection speed 0.5-3mL / h, collecting membrane roller speed 40-60rpm, fiber receiving distance 10-20cm; the calcination temperature is 500-1000℃ and the time is 1-3h.

[0012] Furthermore, the silicon source solution is composed of tetraethyl orthosilicate, solvent, and acid, wherein the mass concentration of tetraethyl orthosilicate in the silicon source solution is 40-60%; the titanium source solution is composed of tetrabutyl titanate, solvent, and acid, wherein the mass concentration of tetrabutyl titanate in the titanium source solution is 50-80%.

[0013] The solvent is one or more of water, ethanol, methanol, acetone, and hexafluoroisopropanol;

[0014] The acid is one or more of glacial acetic acid, nitric acid, and hydrochloric acid, and the amount of acid added is such that the pH value of both the silicon source solution and the titanium source solution is in the range of 2-3.

[0015] The polymer solution is an aqueous solution containing 3-10 wt% water-soluble polymers, including one or more of PEG, PVA, gelatin, and gum arabic.

[0016] The mass ratio of the silicon source solution to the titanium source solution is 1:(2-5); the amount of the polymer solution used accounts for 6-10% of the total mass of the silicon source solution and the titanium source solution.

[0017] Furthermore, the spinning solution is obtained by mixing the silicon source solution and the titanium source solution evenly, then adding the polymer solution and stirring at 25-40°C for 3-5 hours.

[0018] The silicon source solution is obtained by mixing the tetraethyl orthosilicate with the solvent evenly, adding the acid at 25-35°C to adjust the pH to 2-3, and then stirring and reacting for 2-5 hours. The titanium source solution is obtained by mixing the tetrabutyl titanate with the solvent evenly, adding the acid at 25-35°C to adjust the pH to 2-3, and then stirring and reacting for 2-5 hours.

[0019] Furthermore, the binder is aramid pulp and sodium silicate, wherein the mass ratio of aramid pulp to sodium silicate is 1:(5-8), wherein the aramid pulp provides not only interfiber bonding force but also dielectric properties;

[0020] The mass ratio of the potassium hexatite whiskers to the zirconium oxide is 1:5-8.

[0021] Furthermore, the mass ratio of the aluminum silicate fiber to the infrared blocking agent is (8-9):(2-5), and the amount of the binder is 15-30% of the mass of the aluminum silicate fiber.

[0022] The preparation method of the above-mentioned high-temperature resistant heat-insulating fiber composite material includes the following steps:

[0023] (1) Titanium / silicon / carbon inorganic composite nanofiber membrane was prepared by electrospinning and calcination.

[0024] (2) Prepare a paper-forming slurry, and then paper-form it on a wire mesh to obtain a wet sheet substrate;

[0025] The slurry is composed of the following raw materials: aluminum silicate fiber, infrared blocking agent, binder and water;

[0026] (3) The wet sheet substrate, the titanium / silicon / carbon inorganic composite nanofiber membrane layer and the wet sheet substrate are stacked in sequence, then pressed and dehydrated, dried and cured to transform the wet sheet substrate into a fiber sheet layer and bonded to the surface of the titanium / silicon / carbon inorganic composite nanofiber membrane layer to obtain a high temperature resistant heat insulation fiber composite material.

[0027] Furthermore, the slurry concentration is 0.5-1 wt%; the slurry also includes a water-soluble polymer material as an anti-settling agent, the amount of which is 0.5-5% of the mass of the aluminum silicate fiber. The anti-settling agent can prevent the fibers and particles in the slurry from settling during web forming, which is beneficial for the fibers and particles to be formed in a suspended state, thereby improving production efficiency. Preferably, the anti-settling agent is PEG.

[0028] Furthermore; the wet film substrate quantification is at least 300 g / m³. 2 The drying temperature is 100-150℃ and the time is 1-3h. During the drying process, the wet sheet substrate and the titanium / silicon / carbon inorganic composite nanofiber membrane form surface chemical bonds, which then adhere to each other, making the three composite into a whole.

[0029] Beneficial technical effects:

[0030] This invention uses a mixture of titanium sol, silica sol and polymer solution to electrospin a three-dimensional porous nanofiber membrane, and then calcination removes the polymer material, leaving residual carbon, while still obtaining a three-dimensional porous nanofiber membrane. Calcination has no effect on the overall morphology of the membrane, and a flexible, three-dimensional porous, high-temperature resistant inorganic nanofiber membrane can be obtained.

[0031] To achieve better thermal insulation and high-temperature resistance, a wet substrate of a certain thickness is laminated onto the outer surface of the nanofiber membrane. After dehydration and drying, the dehydrated wet substrate solidifies during the drying process. During the solidification process, it bonds with the hydroxyl groups on the surface of the nanofiber membrane, causing the three to adhere together and form a high-temperature resistant thermal insulation fiber composite material. After lamination, it has good tensile strength, can withstand high temperatures up to 1450℃, and has a thermal conductivity of less than 0.025 W / m·K at room temperature. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the cross-sectional structure of a high-temperature resistant heat-insulating fiber composite material, where 1-titanium / silicon / carbon inorganic composite nanofiber membrane layer, 2-fiber sheet layer.

[0033] Figure 2 This is a process roadmap for high-temperature resistant heat-insulating fiber composite materials. Detailed Implementation

[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0035] Unless otherwise specifically stated, the numerical values ​​set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0036] Experimental methods not specifically described in the following examples are generally determined according to national standards; if no corresponding national standard exists, they are performed according to generally accepted international standards or the standards proposed by relevant enterprises. Unless otherwise stated, all parts are parts by weight, and all percentages are weight percentages.

[0037] Sodium silicate is Na2O·nSiO2, where n represents the modulus. The higher the modulus, the less soluble it is in water. At this modulus, the silicate can dissolve well in water at room temperature and has suitable viscosity and strength. The sodium silicate used in the following examples has n = 2.6-2.8.

[0038] The aluminum silicate fibers used in the following examples are high-alumina, cotton-like short fibers with a fiber diameter of 2-4 μm and an aluminum oxide content of 52-55 wt%.

[0039] Example 1

[0040] High-temperature resistant heat-insulating fiber composite material has the following structure:

[0041] The titanium / silicon / carbon inorganic composite nanofiber membrane has bonded fiber sheets on both surfaces, as shown in the schematic diagram below. Figure 1 As shown in the figure, 1 is a titanium / silicon / carbon inorganic composite nanofiber membrane, and 2 is a fiber sheet.

[0042] The fiber sheet 2 is made from the following raw materials: aluminum silicate fiber, infrared blocking agent, and binder; the infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide, and the binder is aramid pulp and sodium silicate glass;

[0043] The high-temperature resistant heat-insulating fiber composite material specifically includes the following steps, and the process flow is as follows: Figure 2 As shown:

[0044] (1) Preparation of the titanium / silicon / carbon inorganic composite nanofiber membrane 1:

[0045] ① Preparation of silicon source solution: Tetraethyl orthosilicate, ethanol and water (equal volume ratio) are mixed evenly, and 2 mol / L hydrochloric acid aqueous solution is added at 30℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 3 hours to obtain silicon source solution, wherein the mass concentration of tetraethyl orthosilicate in the silicon source solution is 50%.

[0046] ② Preparation of titanium source solution: Tetrabutyl titanate, ethanol and water (volume ratio of ethanol to water is 3.5:1) are mixed evenly, glacial acetic acid is added to adjust the pH value to close to 3, and 2 mol / L hydrochloric acid aqueous solution is added at 30℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 4 hours to obtain titanium source solution, wherein the mass concentration of tetrabutyl titanate in the titanium source solution is 50%;

[0047] ③ Preparation of polyvinyl alcohol aqueous solution: Dissolve polyvinyl alcohol (brand name 1788) in hot water, and after cooling, prepare a polyvinyl alcohol aqueous solution with a mass concentration of 8%;

[0048] ④ The silicon source solution and titanium source solution are mixed evenly at a mass ratio of 1:4 and then mixed with a polyvinyl alcohol aqueous solution. The amount of polyvinyl alcohol aqueous solution is 10% of the total mass of the silicon source solution and the titanium source solution to form a homogeneous solution, which is the spinning solution. Electrospinning is performed with the following parameters: spinning voltage 15kV, injection speed of the spinning solution 1mL / h, roller speed of the collecting membrane 50rpm, fiber receiving distance 20cm. A membrane with a thickness of about 150μm is collected and then placed in a muffle furnace at 900℃ for 3h to obtain a titanium / silicon / carbon inorganic composite nanofiber membrane.

[0049] (2) Prepare a formable slurry, then form it on a wire mesh to obtain a wet sheet substrate. The wet sheet substrate quantity is 300 g / m². 2 ;

[0050] The slurry comprises a mixture of raw materials in the following proportions: aluminum silicate fiber, infrared blocking agent, binder, anti-settling agent, and water; wherein the mass ratio of aluminum silicate fiber to infrared blocking agent is 8:5, the amount of binder is 20% of the mass of aluminum silicate fiber, and the amount of anti-settling agent is 3% of the mass of aluminum silicate fiber; and the slurry is prepared with a mass concentration of 0.5%.

[0051] The infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide (the mass ratio of potassium hexatitanate whiskers to zirconium oxide is 1:5), the binder is aramid pulp and sodium silicate (the mass ratio of the two is 1:5), and the anti-settling agent is PEG-800.

[0052] (3) The wet sheet substrate, the titanium / silicon / carbon inorganic composite nanofiber membrane layer and the wet sheet substrate are stacked in sequence and then pressed and dehydrated until the wet sheet substrate has a dryness of about 40%. The wet sheet substrate is dried and cured at 120°C for 2 hours to transform the wet sheet substrate into a fiber sheet layer and bond it to the surface of the titanium / silicon / carbon inorganic composite nanofiber membrane layer to obtain a high temperature resistant heat insulation fiber composite material.

[0053] The high-temperature resistant heat-insulating fiber composite material in this embodiment has a mass loss of less than 20% after being calcined at 1450℃ for 2 hours, indicating good high-temperature resistance.

[0054] Example 2

[0055] High-temperature resistant heat-insulating fiber composite material has the following structure:

[0056] The titanium / silicon / carbon inorganic composite nanofiber membrane has bonded fiber sheets on both surfaces, with the same structure as in Example 1;

[0057] The fiber sheet is made from the following raw materials: aluminum silicate fiber, infrared blocking agent, and binder; the infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide, and the binder is aramid pulp and sodium silicate.

[0058] The high-temperature resistant heat-insulating fiber composite material specifically includes the following steps:

[0059] (1) Preparation of the titanium / silicon / carbon inorganic composite nanofiber membrane:

[0060] ① Preparation of silicon source solution: Tetraethyl orthosilicate, ethanol and water (equal volume ratio) are mixed evenly, and 2 mol / L hydrochloric acid aqueous solution is added at 35℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 2 hours to obtain silicon source solution, wherein the mass concentration of tetraethyl orthosilicate in the silicon source solution is 40%.

[0061] ② Preparation of titanium source solution: Tetrabutyl titanate, ethanol and water (volume ratio of ethanol to water is 3.5:1) are mixed evenly, glacial acetic acid is added to adjust the pH value to close to 3, and 2 mol / L hydrochloric acid aqueous solution is added at 35℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 2 hours to obtain titanium source solution, wherein the mass concentration of tetrabutyl titanate in the titanium source solution is 60%;

[0062] ③ Preparation of polyvinyl alcohol aqueous solution: Dissolve polyvinyl alcohol (brand name 1788) in hot water, and after cooling, prepare a polyvinyl alcohol aqueous solution with a mass concentration of 6%;

[0063] ④ The silicon source solution and titanium source solution are mixed evenly at a mass ratio of 1:5 and then mixed with a polyvinyl alcohol aqueous solution. The amount of polyvinyl alcohol aqueous solution is 8% of the total mass of the silicon source solution and the titanium source solution to form a homogeneous solution, which is the spinning solution. Electrospinning is performed with the following parameters: spinning voltage 18kV, injection speed of the spinning solution 1mL / h, roller speed of the collecting membrane 50rpm, fiber receiving distance 20cm. A membrane with a thickness of about 150μm is collected and then placed in a muffle furnace at 1000℃ for 2h to obtain a titanium / silicon / carbon inorganic composite nanofiber membrane.

[0064] (2) Prepare a formable slurry, then form it on a wire mesh to obtain a wet sheet substrate. The wet sheet substrate quantity is 300 g / m². 2 ;

[0065] The slurry comprises a mixture of raw materials in the following proportions: aluminosilicate fiber, infrared blocking agent, binder, anti-settling agent, and water; wherein the mass ratio of the aluminosilicate fiber to the infrared blocking agent is 9:4, the amount of binder is 30% of the mass of the aluminosilicate fiber, and the amount of anti-settling agent is 4% of the mass of the aluminosilicate fiber; and the slurry is prepared with a mass concentration of 0.5%.

[0066] The infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide (the mass ratio of potassium hexatitanate whiskers to zirconium oxide is 1:6), the binder is aramid pulp and sodium silicate (the mass ratio of the two is 1:7), and the anti-settling agent is PEG-1000.

[0067] (3) The wet sheet substrate, the titanium / silicon / carbon inorganic composite nanofiber membrane layer and the wet sheet substrate are stacked in sequence and then pressed and dehydrated until the wet sheet substrate has a dryness of about 40%. The wet sheet substrate is dried and cured at 130°C for 2 hours to transform the wet sheet substrate into a fiber sheet layer and bond it to the surface of the titanium / silicon / carbon inorganic composite nanofiber membrane layer to obtain a high temperature resistant heat insulation fiber composite material.

[0068] The high-temperature resistant heat-insulating fiber composite material in this embodiment has a mass loss of less than 20% after being calcined at 1450℃ for 2 hours, indicating good high-temperature resistance.

[0069] Example 3

[0070] High-temperature resistant heat-insulating fiber composite material has the following structure:

[0071] The titanium / silicon / carbon inorganic composite nanofiber membrane has bonded fiber sheets on both surfaces, with the same structure as in Example 1;

[0072] The fiber sheet is made from the following raw materials: aluminum silicate fiber, infrared blocking agent, and binder; the infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide, and the binder is aramid pulp and sodium silicate.

[0073] The high-temperature resistant heat-insulating fiber composite material specifically includes the following steps:

[0074] (1) Preparation of the titanium / silicon / carbon inorganic composite nanofiber membrane:

[0075] ① Preparation of silicon source solution: Tetraethyl orthosilicate, ethanol and water (equal volume ratio) are mixed evenly, and 2 mol / L hydrochloric acid aqueous solution is added at 25℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 5 hours to obtain silicon source solution, wherein the mass concentration of tetraethyl orthosilicate in the silicon source solution is 60%.

[0076] ② Preparation of titanium source solution: Tetrabutyl titanate, ethanol and water (volume ratio of ethanol to water is 3.5:1) are mixed evenly, glacial acetic acid is added to adjust the pH value to close to 3, and 2 mol / L hydrochloric acid aqueous solution is added at 25℃ to adjust the pH value to 2-2.5. The reaction is continued to be stirred for 5 hours to obtain titanium source solution, wherein the mass concentration of tetrabutyl titanate in the titanium source solution is 80%.

[0077] ③ Preparation of polyvinyl alcohol aqueous solution: Dissolve polyvinyl alcohol (brand name 1788) in hot water, and after cooling, prepare a polyvinyl alcohol aqueous solution with a mass concentration of 10%;

[0078] ④ The silicon source solution and titanium source solution are mixed evenly at a mass ratio of 1:3 and then mixed with a polyvinyl alcohol aqueous solution. The amount of polyvinyl alcohol aqueous solution is 7% of the total mass of the silicon source solution and the titanium source solution to form a homogeneous solution, which is the spinning solution. Electrospinning is performed with the following parameters: spinning voltage 20kV, injection speed of the spinning solution 1mL / h, roller speed of the collecting membrane 50rpm, fiber receiving distance 20cm. A membrane with a thickness of about 150μm is collected and then placed in a muffle furnace at 800℃ for 3h to obtain a titanium / silicon / carbon inorganic composite nanofiber membrane.

[0079] (2) Prepare a formable slurry, then form it on a wire mesh to obtain a wet sheet substrate. The wet sheet substrate quantity is 300 g / m². 2 ;

[0080] The slurry comprises a mixture of raw materials in the following proportions: aluminum silicate fiber, infrared blocking agent, binder, anti-settling agent, and water; wherein the mass ratio of aluminum silicate fiber to infrared blocking agent is 8:2, the amount of binder is 15% of the mass of aluminum silicate fiber, and the amount of anti-settling agent is 5% of the mass of aluminum silicate fiber; and the slurry is prepared with a mass concentration of 1%.

[0081] The infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide (the mass ratio of potassium hexatitanate whiskers to zirconium oxide is 1:8), the binder is aramid pulp and sodium silicate (the mass ratio of the two is 1:8), and the anti-settling agent is PEG-2000.

[0082] (3) The wet sheet substrate, the titanium / silicon / carbon inorganic composite nanofiber membrane layer and the wet sheet substrate are stacked in sequence and then pressed and dehydrated until the wet sheet substrate has a dryness of about 40%. The wet sheet substrate is dried and cured at 150°C for 1 hour to transform the wet sheet substrate into a fiber sheet layer and bond it to the surface of the titanium / silicon / carbon inorganic composite nanofiber membrane layer to obtain a high temperature resistant heat insulation fiber composite material.

[0083] The high-temperature resistant heat-insulating fiber composite material in this embodiment has a mass loss of less than 20% after being calcined at 1450℃ for 2 hours, indicating good high-temperature resistance.

[0084] Comparative Example 1

[0085] This comparative example is a single-layer titanium / silicon / carbon inorganic composite nanofiber membrane, which is the same as step (1) in Example 1.

[0086] Comparative Example 2

[0087] This comparative example is a single-layer fiber sheet. The preparation process of this layer is the same as step (2) in Example 1. Then, the wet sheet substrate is directly pressed, dehydrated, and dried under the same conditions as step (3) in Example 1.

[0088] The thermal insulation performance and high temperature resistance performance of the above embodiments were tested, and the specific results are shown in Table 1.

[0089] The tensile strength of the material shall be tested at room temperature in accordance with GB / T 36264-2018; the thermal conductivity at room temperature shall be tested in accordance with GB-T32064; and the thermal conductivity at high temperature shall be tested in accordance with YB / T 4130-2005.

[0090] Table 1. Material properties of examples and comparative examples

[0091]

[0092] (The material thickness in Examples 1-3 is approximately 300-400 μm)

[0093] As shown in Table 1, the thermal conductivity of a single titanium / silicon / carbon inorganic composite nanofiber membrane at room temperature is higher than that of a single fiber sheet. However, the thermal conductivity of the single titanium / silicon / carbon inorganic composite nanofiber membrane at 800℃ is much higher than that at room temperature, while the thermal conductivity of the single fiber sheet at 800℃ is lower than that at room temperature. This is because when the surface temperature of the material is above 100℃, infrared thermal radiation becomes the dominant heat transfer mode. Therefore, since the single titanium / silicon / carbon inorganic composite nanofiber membrane does not have the ability to reflect infrared radiation, its thermal insulation performance at high temperatures is poor. Based on this, the present invention forms bonded fiber sheets on the two surfaces of a single titanium / silicon / carbon inorganic composite nanofiber membrane. Potassium hexatitanate whiskers and zirconium oxide, which have infrared reflective properties on the surface and inside of the fiber sheets, are stacked. The particles on the surface contact the nanofiber membrane. Because the stacking increases solid-phase heat conduction, this allows heat inside the nanofiber membrane to be effectively radiated to the outside through the particles at the interlayer interface. Therefore, the thermal conductivity of the final product at a high temperature of 800℃ is only slightly increased compared to room temperature. Since the melting point of potassium hexatitanate whiskers is 1370℃, if the operating temperature exceeds this melting point, the whisker structure will be destroyed, which may affect the thermal insulation performance. Therefore, its usage is relatively low. Zirconia, on the other hand, has high thermal stability (melting point 2700℃) and high infrared reflectivity, thus it can achieve good thermal insulation effects as an interlayer heat-radiating material. The strength of a single fiber sheet is low, and the strength of a single titanium / silicon / carbon inorganic composite nanofiber membrane is also not ideal. Therefore, the three are reactively combined to obtain a composite material with a tensile strength of over 6.5 MPa.

[0094] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-temperature resistant heat-insulating fiber composite material, characterized in that, It has the following structure: The titanium / silicon / carbon inorganic composite nanofiber membrane has bonded fiber sheets on both surfaces; The fiber sheet is made from the following raw materials: aluminum silicate fiber, infrared blocking agent, and binder; The infrared blocking agent is potassium hexatitanate whiskers and zirconium oxide, and the mass ratio of potassium hexatitanate whiskers to zirconium oxide is 1:(5-8). The binder is aramid pulp and sodium silicate, and the mass ratio of the aramid pulp to the sodium silicate is 1:(5-8); The mass ratio of the aluminum silicate fiber to the infrared blocking agent is (8-9):(2-5), and the amount of the binder is 15-30% of the mass of the aluminum silicate fiber. The preparation method of high-temperature resistant heat-insulating fiber composite material includes the following steps: (1) A silicon source solution, a titanium source solution and a polymer solution are mixed evenly to prepare a spinning solution for electrospinning, and then calcined to obtain a titanium / silicon / carbon inorganic composite nanofiber membrane. The silicon source solution is composed of tetraethyl orthosilicate, solvent, and acid, and the mass concentration of tetraethyl orthosilicate in the silicon source solution is 40-60%. The titanium source solution is composed of tetrabutyl titanate, solvent, and acid. The mass concentration of tetrabutyl titanate in the titanium source solution is 50-80%. The amount of acid added is such that the pH value of both the silicon source solution and the titanium source solution is within the range of 2-3. The polymer solution is an aqueous solution containing 3-10 wt% water-soluble polymers; The mass ratio of the silicon source solution to the titanium source solution is 1:(2-5); the amount of the polymer solution used accounts for 6-10% of the total mass of the silicon source solution and the titanium source solution; (2) Prepare a paper-forming slurry, and then paper it on a wire mesh to obtain a wet sheet substrate; The slurry is composed of the following raw materials: aluminum silicate fiber, infrared blocking agent, binder and water; (3) The wet sheet substrate, the titanium / silicon / carbon inorganic composite nanofiber membrane layer and the wet sheet substrate are stacked in sequence, then pressed and dehydrated, dried and cured to transform the wet sheet substrate into a fiber sheet layer and bonded to the surface of the titanium / silicon / carbon inorganic composite nanofiber membrane layer to obtain a high temperature resistant heat insulation fiber composite material.

2. The high-temperature resistant heat-insulating fiber composite material according to claim 1, characterized in that, The electrospinning parameters are as follows: spinning voltage 15-20kV, spinning solution injection speed 0.5-3mL / h, collecting membrane roller speed 40-60rpm, fiber receiving distance 10-20cm; calcination temperature 500-1000℃, time 1-3h.

3. The high-temperature resistant heat-insulating fiber composite material according to claim 1, characterized in that, The solvent is one or more of water, ethanol, methanol, acetone, and hexafluoroisopropanol; The acid is one or more of glacial acetic acid, nitric acid, and hydrochloric acid; The water-soluble polymer includes one or more of PEG, PVA, gelatin, and gum arabic.

4. The high-temperature resistant heat-insulating fiber composite material according to claim 1, characterized in that, The spinning solution is obtained by mixing the silicon source solution and the titanium source solution evenly, then adding the polymer solution and stirring at 25-40°C for 3-5 hours. The silicon source solution is obtained by mixing the tetraethyl orthosilicate with the solvent evenly, adding the acid at 25-35°C to adjust the pH to 2-3, and then stirring and reacting for 2-5 hours. The titanium source solution is obtained by mixing the tetrabutyl titanate with the solvent evenly, adding the acid at 25-35°C to adjust the pH to 2-3, and then stirring and reacting for 2-5 hours.

5. The high-temperature resistant heat-insulating fiber composite material according to claim 1, characterized in that, The slurry concentration is 0.5-1 wt%; the slurry also includes a water-soluble polymer material as an anti-settling agent, and the amount of the anti-settling agent is 0.5-5% of the mass of the aluminum silicate fiber.

6. The high-temperature resistant heat-insulating fiber composite material according to claim 1, characterized in that, The wet sheet substrate has a quantitative content of at least 300 g / m³. 2 The drying temperature is 100-150℃ and the time is 1-3 hours.

Citation Information

Patent Citations

  • Flexible titanium oxide / silicon oxide / carbon composite nanofiber membrane and preparation method thereof

    CN107376888A

  • Fire-resistant thermal-insulation inorganic material, preparation method thereof and fire-resistant thermal-insulation inorganic special-shaped part

    CN112645691A

  • Composite heat insulating aluminium silicate fiber / potassium hexatitanate whisker material and its prepn

    CN1772712A

  • KR1019765910000B1